One-Man Company Policy and Its Impact on Improving Citizen Welfare - Bita Gadsia Spaltani; Muhammad Farid Alwajdi; Uni Tsulasi Putri (Yuridika, 2023)
To facilitate investment for business actors, Law no. 11 of 2020 concerning Job Creation makes changes, deletions, and stipulations to new regulations in several laws. One of the new regulations is to simplify the establishment of limited liability companies (LLCs) through changes to the provisions on company capital, legal entity status, and the company criteria for allowing one person to establish a micro or small business referred to in this research as a one-man company. In its development to date, BPS data from a survey of the impact of the Covid-19 pandemic on approximately 30,000 MSME business actors in 2020 shows that as many as 84 percent of MSMEs experienced a decrease in income during the pandemic, with as many as 24 percent reducing capacity. This research was conducted using a normative juridical approach that examines legal principles as well as related laws and regulations. the legal basis for individual companies is regulated in laws and regulations which include Law Number 11 of 2020 concerning Job Creation (UU Cipta Kerja), Government Regulation Number 7 of 2021 concerning Ease, Protection, and Empowerment of Cooperatives and Micro, Small, and Medium Enterprises, Government Regulation Number 8 of 2021 concerning Authorized Capital of the Company and Registration of Establishment, Amendment.